Estudo da influência do planejamento urbano na paisagem sonora da região central de taubaté-SP - Ferreira de Brito, Luiz Antonio Perrone; Vilela Monteiro, Rita de Cássia Rigotti [UNESP] (My University, 2015)
The urban planning of a city defines quality of life of its inhabitants. There are important parameters which should be included at urban planning as mobility, distribution of spaces and suitability to the local climate. Another important parameter is the soundscape that can be comfortable or even unhealthy. Thus, it is necessary to develop adequate tools to analyze the environmental noise that support urban planning. The acoustic maps, in this context, can assist in the organization of spaces and their uses, providing a better understanding of the current situation or simulating the future soundscape of a region. The objective of this study is to evaluate the influence of urban planning in the soundscape of central Taubaté. The acoustic map was the tool used which indicated high noise areas, incompatible with the welfare of the general population. It was possible to verify the influence of urban planning, that define spacing, traffic routes and other urban facilities, on the soundscape of the analyzed site.
Influence of urban planning study in central region of sound landscape taubaté-SP
Keywords: Acoustic map; Regional development; Urban planning